Il Geoportale Nazionale: un'infrastruttura a supporto delle emergenze (GEOmedia, 2016)
The Italian National Geoportal as a supporting infrastructurefor emergencies.The recent seismic events in the Italian territory have revived the importance of spatial information easily and quickly on the affected areas, targeted initially to the timeliness and effectiveness of the rescues. As often happens, in emergency situations, the difficulties encountered highlight the gaps existing due to an amount of data produced by different institutions oftennot readily integrated with each another. The Italian National Geoportal is the hub to concentrate the access to all geospatial information.